Rapid mHealth - a mobile healthcare application development framework. (2017) - Kumaresan, Senthil; Srinivas, Satya Sai; Maitra, Anutosh; Kuntagod, Nataraj
A new philosophy and architecture of rapid mobile healthcare application development is presented here. Many monolith applications developed on the Lambda architecture had been successful earlier, but of late, this architecture is found inadequate when deployed for different stakeholders. Today's healthcare applications handle large volume of streaming data obtained from dispersed devices. The architecture is to support multiple use cases as the business models are evolving and the products have to be malleable enough to support different functions. This paper describes a working architecture on which mobile healthcare applications can be rapidly built through ingestion and processing of voluminous streaming data. The use of micro-services keeps this architecture flexible. On the client side, application platform as a service (APaaS) frameworks are employed to assist quick development and validation of solutions. Findings from some successfully deployed mobile healthcare applications based on this architecture are also discussed.